Cyberbullying victimisation and its association with depression, anxiety and stress among female adolescents in Deumai Municipality, Nepal: a cross-sectional survey - Shishir Paudel; Anisha Chalise; Saloni Pandey; Santosh Khadka; Anisha Limbu (BMJ Open)
Objective To estimate the prevalence of cyberbullying and its association with depression, anxiety and stress among female adolescents attending higher secondary schools in Deumai Municipality, Nepal.Design Cross-sectional survey study.Setting The survey was conducted at all available higher secondary schools of Deumai Municipality, Ilam District, Nepal, from February to April 2022.Participants A total of 501 female adolescents enrolled in grades 11 and 12 were included in the study. All eligible participants available on the day of data collection were approached until the calculated sample size was reached.Outcome measures The study assessed the prevalence of cyberbullying victimisation, along with the prevalence of depression, anxiety and stress and their associated factors. The level of psychological distress was explored using the Depression Anxiety Stress Scale-21. Pearson’s χ2 test and multivariate logistic regression analysis were applied to determine the association between psychological distress and related variables, including cyberbullying victimisation, at 95% CI and 5% level of significance.Results Nearly a third (32.5%) of the female adolescents included in the study had experienced cyberbullying. The overall prevalence of depression, anxiety and stress was 46.5%, 52.7% and 34.9%, respectively. Cyberbullying victims were observed to have increased odds of experiencing depression (adjusted OR (aOR): 1.64, 95% CI 1.11 to 2.42), anxiety (aOR: 2.49, 95% CI 1.67 to 3.70) and stress (aOR: 2.59, 95% CI 1.74 to 3.86) in comparison with non-victims.Conclusion Cyberbullying victims are significantly more likely to experience psychological distress. There is an urgent need to strengthen cybersecurity and to have strong legislative measures to address cyberbullying in order to safeguard the mental health of adolescents in the digital age.